Production of Z0 bosons in elastic and quasi-elastic ep collisions at HERA - Abramowicz, H; Abt, I; Adamczyk, L; Adamus, M; Aggarwal, R; Antonelli, S; Antonioli, P; Antonov, A; Arneodo, M; Arslan, O; Aushev, V; Aushev, Y; et al. (2013)
The production of Z0 bosons in the reaction ep→eZ0p(*), where p(*) stands for a proton or a low-mass nucleon resonance, has been studied in ep collisions at HERA using the ZEUS detector. The analysis is based on a data sample collected between 1996 and 2007, amounting to 496pb-1 of integrated luminosity. The Z0 was measured in the hadronic decay mode. The elasticity of the events was ensured by a cut on ηmax<3.0, where ηmax is the maximum pseudorapidity of energy deposits in the calorimeter defined with respect to the proton beam direction. A signal was observed at the Z0 mass. The cross section of the reaction ep→eZ0p(*) was measured to be σ(ep→eZ0p(*))=0.13±0.06(stat.)±0.01(syst.) pb, in agreement with the Standard Model prediction of 0.16 pb. This is the first measurement of Z0 production in ep collisions. © 2012 Elsevier B.V.